“Like Little Knives, Stabbing Me”: The Impact of Microaggressions on LGBTQ+ Teens and Their Parents in the Church of Jesus Christ of Latter-Day Saints - Sorrell, Sydney A. (Journal for the scientific study of religion, 2024)
Lesbian, gay, bisexual, transgender, and queer/questioning (LGBTQ+) teens raised in the Church of Jesus Christ of Latter-Day Saints (CJCLDS) experience microaggressions in their religious contexts. Active Latter-Day Saint parents of LGBTQ+ teens also face microaggressions in their religious environments, despite not holding an LGBTQ+ identity. We examined the impacts of microaggressions and the coping strategies used by 19 dyads of LGBTQ+ teens and their Latter-Day Saints (LDS) parents to understand how current microaggression and minority stress theories map on to their experiences. Participants described feelings of anger, sadness, fear, disgust, and surprise as well as increases in relationship conflict due to microaggressions. Both parents and teens described religious doubt, disengagement from religion, and feelings of dis-belonging and disillusionment because of microaggressions. These findings may provide insight into the ways that minority stressors threaten the health and faith of LGBTQ+ teens and their families. Finally, participants reported using a range of coping strategies to buffer against the effects microaggressions, including social support, emotion-focused, problem-focused, meaning-making, and faith-based approaches to coping. Overall, parents and teens reported similar impacts and ways of coping with microaggressions, demonstrating how minority stress process may be at play on a family-systems level in the CJCLDS.